Studies on Afforestation for Controlling Avalanche and Improving Eco-environment in Mgh Altitude - Singh, Narendra; Singh, Gursharan; Kumar, Amod; Stobden, Tsering (Indian Forester, 2010)
Performance of different high altitude plant species was observed in avalanches affected area at the top ofJawahar Tunnel (3200 m amsl) situated on Jammu-Srinagar National Highway (NH-1A) near Banlhal, J &K. Seabuckthron (HippopluIe rhamnoide), willow (Salix alba), poplar (Populus nigra) and elegnus (Elaeagnus angustifolia) saplings were planted in first week of April 2008 at the site under the study. Higher plant survival percentage, number of branches/plant and number of leaves/branch were recorded in seabuckthorn followed by willow after three months and sixteen months of plantation. Maximum length of branch and percentage of stem diameter increased were recorded with willow than all the other plant species at both the stages. Overall better growth performance of all the studied species were observed at northern aspect as compared to the southern aspect.